Intelligent Character Recognition system for visually impaired people - Alam, Md. Sabbir; Faisal, Bhuiyan Washek; Hasan, Mohammad Al Imran (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.